Measuring inhibitory control in emotionally dysregulated young and old adults using Stop Signal Paradigm - Sembi, Gurnoor Kaur (My University, 2026)
Inhibitory Control is the ability to supress pre-initiated responses, a fundamental executive process sensitive to emotional context as well as age related cognitive change. Increasing evidence show how emotional valence and emotion regulation difficulties independently modulate inhibitory processes, however little research has studied these factors together in young and old adult sample. The present study fills in this gap by examining how emotional valence, age related differences and differences in emotional regulation among people together influence inhibitory performance using Emotional Stop Signal Paradigm. A sample 64 participants (30 young; 34 old) was assessed on task and difficulties in emotion regulation. Negative emotional conditions showed greater inhibitory control performance which was reflected by longer Stop Signal Delay (SSDs) and shorter Stop Signal Reaction Time (SSRT), indicating the increased caution of the cognitive system towards environmental threat. Older Adults exhibited longer SSRTs compared to young adults suggesting the age-related slowing of inhibitory mechanism. Importantly, young and old adults both were modulated by emotional valence in similar manner, that can be interpreted through the Socioemotional Selectivity Theory that reflects the. sophistication of emotion regulation resources with increase in age. Higher scores in difficulties in emotion regulation scale were associated with lower stop success, indicating that emotional dysregulation hampers the executive resources needed for efficient response inhibition. Taken together, these findings highlight the process of inhibitory control sensitive to emotional contexts, cognitive aging and individual regulatory capacity, unfolding a meaningful understanding of real-world processing of impulse control in emotional situations.
Keywords: Emotional Dysregulation; Cognitive Aging; Stop Signal Paradigm; Inhibitory Control; Socioemotional Selectivity theory